2015
DOI: 10.15414/jmbfs.2015.4.5.467-472
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Milk-Clotting Protease Production by a Local Isolate of Aspergillus Niger Ffb1 in Solid-State Fermentation

Abstract: The need to surmount the limitation of obtaining rennin, has been actively pushed researches to find new substitutes that present high milk-clotting activity which enables the production of high yields of cheese. In this study, the production of extracellular milk-clotting protease by locally isolated fungal specie, Aspergillus niger FFB1 under solid-state fermentation (SSF) using cheep agro-industrial byproduct (wheat bran) was optimized. The effects of several physicochemical and environmental factors were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 31 publications
3
20
2
2
Order By: Relevance
“…This could be due to lamentous fungi preferred SSF for production of enzymes (18). Similar protease activities were recorded by Aspergillus species (26)(27)(28)(29) and Mucor species under SSF.…”
Section: Discussionsupporting
confidence: 65%
“…This could be due to lamentous fungi preferred SSF for production of enzymes (18). Similar protease activities were recorded by Aspergillus species (26)(27)(28)(29) and Mucor species under SSF.…”
Section: Discussionsupporting
confidence: 65%
“…Although the particle size of each substrate was not determined, the difference may be due to differences in particle size between wheat bran and the other three substrates which is partly related to porosity [25]. Wheat bran is considered as the best substrate for the production of acid protease from A. oryzae MTCC 5341 [4], other Aspergillus species [20,26], and Mucor sp. [27].In the present study, both wheat bran moistened with a mineral solution and wheat bran moistened with HCL were used for milk-clotting protease production; however, the result showed that wheat bran moistened with HCL was better for MCP production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of initial moisture content on enzyme production was tested by moistening substrate using distilled water in different percentages of moisture content, 45, 50, 55, 60, 65, and 70%, to find out the best percentage for enzyme production [20]. The milk-clotting and protease activities were assayed according to [6].…”
Section: Effect Of Moisture Contentmentioning
confidence: 99%
“…Aspergillus tamari and Penicillium pinophillum also demonstrated great milk-clotting protease production in liquid medium containing whey as one of the main substrates (Benlounissi et al, 2014). In the study of Bensmail et al (2015), A. niger produced proteolytic enzymes with wheat bran as substrate in submerged and solid-state fermentation. Castro et al (2014) also studied milk-clotting enzymes secreted by A. niger.…”
Section: Protease Production and Milk-clotting Activitymentioning
confidence: 99%
“…Submerged fermentation (SmF) is a well-known process to produce enzymes by the growing of microorganisms in liquid substrate or in the presence of excess water while solid-state fermentation (SSF) involves the growth of microorganisms on solid substrates in the absence or near absence of free water in the space between particles (Bensmail et al, 2015;Singhania et al, 2010). Because of need for new microbial milk-clotting proteases sources due the shortage of rennet and the increase demand for cheese, the aim of this study was to investigate the protease production by A. flavo furcatis DPUA 1608 in submerged and solid state fermentation and also certify the nonproduction of aflatoxin by this species.…”
Section: Introductionmentioning
confidence: 99%